Cholesterol Retards Senescence in Bone Marrow Mesenchymal Stem Cells by Modulating Autophagy and ROS/p53/p21Cip1/Waf1 Pathway. (15th September 2016) - Zhang, Mingyu; Du, Yue; Lu, Renzhong; Shu, You; Zhao, Wei; Li, Zhuoyun; Zhang, Yu; Liu, Ruixue; Yang, Ti; Luo, Shenjian; Gao, Ming; Zhang, Yue; et al.
Abstract : In the present study, we demonstrated that bone marrow mesenchymal stem cells (BMSCs) of the 3rd passage displayed the senescence-associated phenotypes characterized with increased activity of SA- β -gal, altered autophagy, and increased G1 cell cycle arrest, ROS production, and expression of p53 andp 21 C i p 1 / W a f 1 compared with BMSCs of the 1st passage. Cholesterol (CH) reduced the number of SA- β -gal positive cells in a dose-dependent manner in aging BMSCs induced by H2 O2 and the 3rd passage BMSCs. Moreover, CH inhibited the production of ROS and expression of p53 andp 21 C i p 1 / W a f 1 in both cellular senescence models and decreased the percentage of BMSCs in G1 cell cycle in the 3rd passage BMSCs. CH prevented the increase in SA- β -gal positive cells induced by RITA (reactivation of p53 and induction of tumor cell apoptosis, a p53 activator) or 3-MA (3-methyladenine, an autophagy inhibitor). Our results indicate that CH not only is a structural component of cell membrane but also functionally contributes to regulating cellular senescence by modulating cell cycle, autophagy, and the ROS/p53/p 21 C i p 1 / W a f 1 signaling pathway.